Engine combustion, performance, and emission characteristics of hermetia illucens larvae oil in a compression ignition engine - Mohd Kamal, Kamarulzaman (2021)
As biofuel grabbed the world’s attention as one of the potential alternative fuels, it’s also has promoted a drastic debate due to its present production status, such as the longterm impact on food prices, high cost, arable land requirement, and vegetable oil dependency. Therefore, lower cost feedstock can be used for biofuel production has been investigated. The immature life stage of certain insects is capable to consume numerous organic wastes for fat accumulation. The amount of fat produced is different among various insects order and species. It expected to produce about 1.5 to 77.0% fat content from its dry matter. This indicates that every 100 g dried matters of the insect comprise approximately fat about 1.5 to 77.0 g. Therefore, this high fat containing insect has the potential to serve as a biofuel feedstock. In this study, the insect larval grease extracted from Hermetia illucens (the black soldier fly) with the potential to produce fat content approximately 15.5 to 34.8% of its dry matters (about 15.5 to 34.8 g of fat content from 100 g of its dried matters) was investigated by looking at its potential as a substitute for vegetable oil and to reduce dependency on petroleum resources. The research is motivated by the need to critically examine the effect of Hermetia illucens larvae oil mixed with diesel fuel on engine combustion, performance, and emission characteristics of a single-cylinder direct injection compression ignition engine. The experiment was performed using a single cylinder unmodified Yanmar TF120M compression ignition engine at a constant speed of 1500 rpm under various engine loads. The neat of Hermetia illucens larvae oil and its blends (B25, B50, B75, and B100) were utilized in the engine in order to identify its combustion, performance, and emission characteristics. Regression models were developed using the response surface methodology to predict the significant of engine performance and emission parameters with fuel property’s changing trend. The results revealed that in-cylinder pressure, heat release rate, and the ignition delay were reduced by an average of 2.27%, 12.89%, and 12.36%, respectively. The brake specific fuel consumption and exhaust gas temperature increased 32.92% and 4.70%, respectively than that of diesel fuel. The brake thermal efficiency was discovered to be lower by 30.0% compared to diesel fuel. The finding also shows that carbon monoxide, carbon dioxide, and unburned hydrocarbon emissions increased by 86.68%, 15.04%, and 950.00%, respectively with the addition of Hermetia illucens larvae oil. The nitrogen oxides emissions indicates good improvement trend by 14.67% reduction as compared to diesel fuel at all the engine loads. Analysis of variance (ANOVA) of the experimental results at 95% confidence level exposed that the developed models are significant. Comparison of experimental output with those predicted by the developed models indicated close proximity having high correlation coefficients R2 for the various response variables. Overall, this study concluded that the Hermetia illucens larvae oil possesses a high potential to be utilized as a promising alternative fuel for compression ignition engines in the future.